The glass kitchen - Lee, Linda Francis (St. Martin's Press, 2014)
"Portia Cuthcart and her two sisters find their way from Texas to Manhattan over the years, the heiresses to a dilapidated brownstone on the Upper West Side. Portia is running from a bad divorce and the knowledge that she has always been a little bit different, a little bit strange: the talented cook who knew exactly what to serve on what occasion, even to the point of predicting events that hadn't even happened yet. But she doesn't cook anymore. She has tamped down this "knowing." It has caused her way too many problems. When she meets twelve-year-old Ariel Kane, she sees a girl in desperate need of a mother and a family in dire need of fried chicken, biscuits, and strawberry rhubarb pie. Widowed Gabriel Kane has his hands full with two daughters on the cusp on womanhood, plus the Kane family have so many secrets and rivalries of their own. Ariel, especially, must find a way to bring them all together with the help of Portia: the non-cook, the non-believer in happy endings. Portia, who just might have to rethink the pages of her own story and take a few chances to claim what she wants deep down inside."--